COMPARISON ANALYSIS OF BANDWIDTH SPEED USING MIKROTIK ROUTERBOARD 750 - Ericky Benna Perolihin Manurung; Mutammimul Ula (Jurnal Techno Nusa Mandiri, 2023)
The purpose of this study is to analyze and optimize bandwidth management at aminet cafes which often experience bandwidth leakage problems where users can access the internet without any bandwidth restrictions. Bandwidth management in this study uses a proxy and Queue Tree with the Network Development Life Cycle (NDLC) system development method. The results of the study show that bandwidth management runs optimally with balanced upload and download speeds for each user because the bandwidth distribution process has been carried out. The average upload speed is 121 kbps and the download speed is 732kbps.